Perancangan Website UMKM Warung Pasinggahan Bendungan Universitas Andalas Menggunakan Visual Studio Code Untuk Pengembangan Usaha dan Promosi Produk. - Gugum Gumilang; Agil Nadhatul Isra; Mhd Idris (CV. ITTC INDONESIA, 2024)
Warung Pasinggahan Dam Unand is a Micro, Small and Medium Enterprise located right behind the Andalas University campus and Padang State Polytechnic This research aims to explore and analyze the existence of Warung Pasinggahan Dam Unand as one of the culinary places that is popular among students and visitors. The methods used in this research are in-depth interviews and field research. The results showed that Warung Pasinggahan not only functions as a place to eat, but also as a space for social interaction for students. The diverse menu and affordable prices are the main attractions, while the cozy atmosphere and strategic location support repeat visits. This research is expected to provide deeper insights into the dynamics of culinary places in educational environments and their contribution to the local community